The Imperative for Strengthening Soil Information Systems (SISs) in Africa: Reflections and Key Insights from Practice - African Union Development Agency- NEPAD (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This policy brief presents the case for scaling and integrating soil information systems (SISs) as a foundational step toward addressing Africa’s urgent challenges of land degradation, food and nutrition insecurity, biodiversity loss, and climate change. With over 65% of productive land degraded and millions of smallholder farmers struggling to grow food in nutrient-depleted soils, the need for healthy, resilient soils has never been more critical. This policy brief emphasizes that healthy soil underpins sustainable agricultural systems and delivers essential ecosystem services such as carbon sequestration, drought resilience, and erosion control. It calls on African Union Member States to develop cohesive, evidence-based monitoring frameworks that enable targeted, locally relevant soil restoration and investment decisions.